The Effect of Clay Minerals on Phosphorus Fixation and Release Reactions /Review - Dadoosh, Awatif Hameed; Naser, Kadhim Makki (American Journal of Biology and Natural Sciences, 2025)
Phosphorus is considered one of the most essential macronutrients required for plant growth; however, its availability in soil is often limited and insufficient to meet plant demands due to fixation and precipitation reactions. These processes are significantly influenced by the soil's pH level. In acidic soils, the dominance of iron and aluminum oxides both in crystalline and amorphous forms contributes to the reduced solubility of inorganic phosphorus. This occurs as phosphorus becomes fixed on positively charged surfaces or forms low-solubility compounds with iron and aluminum. Moreover, interactions with kaolinite minerals further limit phosphorus mobility in such soils. Conversely, in alkaline soils, phosphorus tends to react with calcium ions, resulting in the formation of slightly soluble calcium phosphates. These chemical interactions reduce the efficiency of phosphorus fertilization and its subsequent availability to plants. Accordingly, this article aims to investigate the influence of various clay mineral types on the mechanisms of phosphorus fixation and its subsequent release in soils.